HUBUNGAN KADAR ASAM URAT DENGAN KEPARAHAN PENYAKIT PARKINSON - Elvina Zuhir; Ratih Ayuningtiyas; Putri Wulandini (LPPM Universitas Abdurrab, 2025)
Abstract In recent centuries, there has been an increase in life expectancy, whereas, in developed countries, the average life span is longer than in previous generations. This longer lifespan has also led to a rise in cases of chronic neurological diseases, such as Parkinson's disease. Parkinson's disease is the second most common neurodegenerative disorder after Alzheimer's disease. Its prevalence is 0.5 to 1 % after age 65 and 1 to 3 % after age 80; the disease is rare in individuals younger than 50. A decrease in dopamine levels in Parkinson's Disease produces symptoms such as bradykinesia, stiffness, tremor at rest, and postural imbalance, which become noticeable when 70-80% of dopamine-producing neurons are lost. Intracellular dopamine metabolism is susceptible to free radical production, exposing dopaminergic cells to a greater risk of oxidative stress toxicity. Urate, or uric acid, as a purine metabolite, is a powerful natural antioxidant that plays an essential role in eliminating free radicals. The study was conducted on 21 patients with Parkinson's at Bangkinang Hospital in 2023. Data collection is done by conducting a physical examination to determine the severity of Parkinson's disease and then analyzing uric acid levels. From the results of Spearman’s analysis, a p-value of 0.872 was obtained, which showed no relationship between uric acid levels and the severity of Parkinson's disease. Keywords: Parkinson's disease, uric acid, disease severity Abstrak Dalam beberapa abad terakhir, telah terjadi peningkatan harapan hidup, sedangkan, di negara maju, rentang hidup rata-rata lebih lama daripada generasi sebelumnya. Umur yang lebih panjang ini juga menyebabkan peningkatan kasus penyakit neurologis kronis, seperti penyakit Parkinson. Penyakit Parkinson adalah gangguan neurodegeneratif paling umum kedua setelah penyakit Alzheimer. Prevalensinya adalah 0,5 hingga 1% setelah usia 65 dan 1 hingga 3% setelah usia 80; Penyakit ini jarang terjadi pada individu yang lebih muda dari 50 tahun. Penurunan kadar dopamin pada penyakit Parkinson menghasilkan gejala seperti bradikinesia, kekakuan, tremor saat istirahat, dan ketidakseimbangan postural, yang menjadi nyata ketika 70-80% neuron penghasil dopamin hilang. Metabolisme dopamin intraseluler rentan terhadap produksi radikal bebas, mengekspos sel-sel dopaminergik untuk risiko yang lebih besar toksisitas stres oksidatif. Urat, atau asam urat, sebagai metabolit purin, adalah antioksidan alami yang kuat yang memainkan peran penting dalam menghilangkan radikal bebas. Penelitian dilakukan pada 21 pasien Parkinson di Rumah Sakit Bangkinang pada tahun 2023. Pengumpulan data dilakukan dengan melakukan pemeriksaan fisik untuk mengetahui tingkat keparahan penyakit Parkinson kemudian menganalisis kadar asam urat. Dari hasil analisis Spearman, diperoleh p-value sebesar 0,872 yang menunjukkan tidak ada hubungan antara kadar asam urat dengan tingkat keparahan penyakit Parkinson. Kata kunci: Penyakit Parkinson, asam urat, keparahan penyakit